PERANAN SIARAN GURU KELILING LPP-RRI BANDA ACEH TERHADAP PEMBELAJARAN ANAK-ANAK DISABILITAS DI MASA PANDEMI - Reni Juliani; Mardani Mardani (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2021)
The purpose of this study was to find out in depth the role of the LPP-RRI Banda Aceh Mobile Teacher Broadcast program for children with disabilities during the pandemic. The type of research used in this research is descriptive. The sources of this research come from literature studies, journals, and related articles. The results showed that the mobile teacher broadcast program was effective for children with disabilities compared to those who had to study online. Parents feel happy because learning like this is more effective than the online system.Keywords: Mobile teacher, disability, pandemic